2020
DOI: 10.3390/life10040035
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Primordial Acetyleno/Carboxydotrophic Core Metabolism

Abstract: Carbon fixation, in addition to the evolution of metabolism, is a main requirement for the evolution of life. Here, we report a one-pot carbon fixation of acetylene (C2H2) and carbon monoxide (CO) by aqueous nickel sulfide (NiS) under hydrothermal (>100 °C) conditions. A slurry of precipitated NiS converts acetylene and carbon monoxide into a set of C2–4-products that are surprisingly representative for C2–4-segments of all four central CO2-fixation cycles of the domains Bacteria and Archaea, whereby some o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 33 publications
(43 reference statements)
1
16
0
Order By: Relevance
“…In earlier work starting from acetylene, CO or cyanide under simulated hydrothermal conditions, we showed that nickel, especially NiS, is a potent catalyst for the formation of organic molecules, such as fatty acids, intermediates serving in biological carbon fixation and amino acids [ 11 , 12 , 28 ]. As we can now show, NiS catalyzes additionally the formation of thiophene from acetylene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In earlier work starting from acetylene, CO or cyanide under simulated hydrothermal conditions, we showed that nickel, especially NiS, is a potent catalyst for the formation of organic molecules, such as fatty acids, intermediates serving in biological carbon fixation and amino acids [ 11 , 12 , 28 ]. As we can now show, NiS catalyzes additionally the formation of thiophene from acetylene.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown earlier that acetylene is also an excellent source for primordial carbon fixation, especially in combination with carbon monoxide, e.g., for the synthesis of short chain fatty acids [ 11 ] and intermediates of extant carbon fixation cycles [ 12 ]. On Earth, acetylene is present in fumarolic exhalations [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflexive in this context simply refers to a closure property in which the product of the final catalyst provides the substrate for the first. The relevance of these control networks is almost certainly validated by their homologies to various chemical cycles, such as the formose cycle [31], the Krebs cycle [32], and related core metabolisms [33]. The more recent studies strengthen arguments favoring metabolism first, autotrophic pre-biology forms.…”
Section: Biological Process Control: Feedback Autocatalysis Hypercymentioning
confidence: 94%
“…That afforded a means to systematize the bewildering array of networks for modeling the emergence of life-like properties built by computational theorists as "Reflexive Autocatalytic Food Sets" (RAFS [27][28][29][30][31][32][33]) or GARDs [34], and show that they have the same formal structure [19]. The relevance of these control networks is almost certainly validated by their homologies to various chemical cycles, such as the formose cycle [35], the Krebs cycle [36], and related core metabolisms [37]. More recent studies strengthen arguments favoring metabolism first, autotrophic pre-biology forms.…”
Section: Biological Process Control: Feedback Autocatalysis Hypercymentioning
confidence: 99%